The Judicial Considerations in Determining Criminal Sanctions for Complicity in Promoting Online Gambling Sites (A Study of Decision No. 967/Pid.Sus/2024/PN Tjk) - Hartono, Bambang; Limantara, Benny Karya; Alfaruki, Ikbal (The Future of Education Journal, 2025)
This research is motivated by the rise of online gambling site promotions through social media, particularly by influencers, which has significantly impacted the increase in gambling practices among the public. The development of information technology not only brings positive impacts but also poses threats in the form of cybercrime, including online gambling promotions. One of the actual cases that is the focus of this study is the case of the promotion of an online gambling site by a woman who was then prosecuted at the Tanjung Karang District Court. The problem formulation in this research covers two main things: the form of accountability of the perpetrator of the crime of online gambling promotion, and the judge's considerations in determining criminal sanctions for the perpetrator. This study aims to analyze the legal basis and juridical considerations used by judges in issuing decisions against defendants who participated in the promotion of online gambling sites. The method used in this research is a normative and empirical juridical approach, with data collection through literature studies and direct interviews with relevant parties, such as investigators, prosecutors, and judges. The data obtained is analyzed qualitatively to describe aspects of criminal responsibility and judges' considerations in depth based on the decision of case Number: 967/Pid.Sus/2024/PN Tjk. The results of the study indicate that the defendant in this case was subject to sanctions based on Article 27 paragraph (2) Jo. Article 45 paragraph (3) of the ITE Law, Jo. Article 55 paragraph (1) point 1 of the Criminal Code for participating in promoting online gambling sites through an Instagram account. The judge considered various aspects, including evidence, the defendant's confession, and the social impact of the action. The defendant was sentenced to 1 year and 4 months in prison and a fine of Rp. 10,000,000.00. The judge's considerations in handing down the verdict included aggravating factors, such as not supporting government efforts to eradicate gambling, and mitigating factors, such as the defendant's cooperative attitude during the trial. This demonstrates the importance of the judge's role in balancing aspects of justice and legal certainty, especially in cases involving the misuse of digital media for unlawful purposes. The author recommends that efforts to prevent the promotion of online gambling be strengthened through monitoring digital platforms and educating the public, especially the younger generation, regarding the legal and social impacts of involvement in online gambling activities. In addition, law enforcement officers are expected to improve coordination and responsiveness to new modes that utilize social media for cybercrime.